From Relational Care Quality to Digital Health Literacy: The Mediating Role of Patient Engagement and Moderating Role of Patient Satisfaction - Made Santika; Thomas Stefanus Kaihatu; Timotius Febry Christian (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – Indonesian regional hospitals face pressure to expand digital health services, yet whether patient engagement builds the digital literacy needed to use them, and under what conditions, remains untested. This study examined whether perceived care continuity, practitioner communication, and perceived empathic care predict patient digital literacy directly and indirectly through patient engagement, and whether patient satisfaction moderates the engagement-to-digital-literacy path. Design/methodology/approach – This study used partial least squares structural equation modeling (PLS-SEM) on data from 400 patients across three Type B hospitals in Makassar, Indonesia. Finding/Results – All three relational care quality constructs significantly predicted patient engagement (R² = .499), which significantly predicted digital literacy (β = .531, R² = .475). Care continuity and communication retained significant direct effects on digital literacy, while empathic care operated entirely through engagement. Patient satisfaction alone did not predict digital literacy, but its interaction with engagement was significant (β = .238), nearly tripling the effect from β = .293 among less-satisfied patients to β = .769 among more-satisfied patients. Confirmatory tetrad analysis supported the reflective measurement model, and reliability and validity criteria were met. Originality/Value – Findings suggest patient engagement functions as a developmental pathway to digital literacy, conditional on satisfaction, offering hospital managers a sequencing rationale for pairing digital-service rollouts with service-quality improvement.